Disharmonization of Arbitral Judgments and District Courts in Guarantee Bank Claims Disputes - Aditama Candra Kusuma; Heru Sugiyono; Muthia Sakti (PALAR | PAKUAN LAW REVIEW, 2026)
This research is motivated by the phenomenon of dualism of decisions between arbitration institutions and district courts in the case of bank guarantee claims which have implications for legal certainty for the principal or customer. In practice, often the arbitral institution decides that the principal is not proven to be in default, while the District Court orders the disbursement of the bank guarantee to the guarantor. This condition creates a normative conflict between the principle of finality and binding in the arbitration award and the judicial authority of the district court. This study uses normative legal research methods with a statute approach, a comparative approach, and a case study approach, and a case study approach, and relies on secondary data from laws and regulations, literature, and related court decisions. The results of the study show that normatively, arbitral awards have a legal status on par with district court decisions and are final and binding, but in practice there are still judicial interventions that cause legal uncertainty. The dualism of the decision has an impact on economic losses, reputation, and the effectiveness of business dispute resolution. Using Gustav Radbruch's theory of legal certainty, this study emphasizes the importance of consistency in the application of the principle of final and binding and the harmonization of authority between arbitration and general courts to ensure legal certainty, justice, and stability of the business climate in Indonesia.   Keywords: Arbitration, Bank Guarantee, Legal certainty.